Effects of a sustained-release multi-trace element ruminal bolus on sex ratio, reproductive traits and lambs growth in synchronized Afshari ewes - Eslam Abdollahi; Hamid Kohram; Mohammad hossein Shahir; Mohammad hossein Nemati (The Iranian Journal of Veterinary Science and Technology, 2015)
The objective of the present study was to investigate the effects of a sustained-release multi-trace element ruminal bolus on sex ratio, the reproductive performance and lambs growth of Afshari ewes. Eighty Afshari cycling ewes during breeding season were used in the trial. The animals were synchronized using CIDR for 14 days and assigned into 4 groups including: group 1 (n=20) received a single Ferrobloc bolus four weeks prior to CIDR insertion following 400 IU eCG on CIDR removal, group 2 (n=20) received two boluses four weeks prior to CIDR insertion following 400 IU eCG on CIDR removal, group 3 (n=20) received only 400 IU eCG on CIDR removal and group 4 (n=20; control) received no bolus and no eCG. Growth traits were analyzed using the mixed procedure of SAS. Number of observations (lambing rate, litter size, barren rate and the male / female lamb rate) in different groups was compared using the Chi-Square test. Results showed that ruminal bolus can play an indirect role in skewing sex ratio toward male offsprings. Given 1 or 2 sustained-release multi-trace element ruminal boluses four weeks before synchronization programme using eCG, causes the pregnancy of all ewes. Of the four treatments tested, the 2 boluses+eCG showed superiority on reproductive performancein terms of lambing rate (150%) and litter size (150%) in Iranian Afshari ewes during breeding season. Also, bolus supplementation enhances lamb body weight at birth up to 60 days of age.